Nativist attitudes and opportunistic support for democracy. Issue 1 (2nd January 2023) - Kokkonen, Andrej; Linde, Jonas
Abstract: Do nativists differ from other citizens in their attitudes towards democracy? In this article it is demonstrated that nativism goes hand in hand with preferences for a type of democracy where the interests of the natives should prevail, even at the cost of diminished minority rights, checks and balances, and other constraints on executive power. Liberal representative democracy is not for nativists. It is also shown that nativists seem to believe that the end justifies the means when it comes to different forms of decision making, and that this opportunistic trait usually translates into support for more direct democracy and scepticism towards representative democracy, because nativists tend to believe that they are in the majority (even if they are not). This article concludes that this tendency may in fact be a blessing of sorts, as it keeps nativists from supporting alternatives to democracy. Supplemental data for this article can be accessed online at: https://doi.org/10.1080/01402382.2021.2007459 .